UPAYA PENINGKATAN PEMAHAMAN MEMBACA SISWA KELAS XII IPA 1 SMAN 1 PASAMAN DALAM TEKS DISCUSSION MELALUI TEKHNIK BERDEBAT - Haswinda Abdi (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Abstract Based on the assessment of learning outcomes in the English lesson about reading reading text that genre "Discussion" in grade XII students IPA.1 SMAN 1 Pasaman, found the value is still very low or did not reach KKM is 80. The average score of reading comprehension of students is still is under the KKM. The purpose of this study is to describe and obtain information about efforts to improve students' reading comprehension in English subjects on text in the form of discussion through the model of Arguing. This research is a classroom action research. The research procedures in this research include planning, action, observation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 30 students of class XII IPA1 SMAN 1 Pasaman. The data were collected using observation sheet and daily test. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the model of arguing can improve students' reading comprehension in English subjects, especially text in the form of 'Discussion' in SMAN 1 Pasaman. The reading comprehension of students increases from cycle I to cycle II. The reading comprehension of students in cycle I was 48.7 (Less) increased to 83.5 (good) with an increase of 34.8.Keywords: Understanding reading, DiscussionText, Technique argue